Does Third-Party Fact-Checking Increase Trust in News Stories? An Australian Case Study Using the "Sports Rorts" Affair. Issue 5 (14th June 2022) - Carson, Andrea; Gibbons, Andrew; Martin, Aaron; Phillips, Justin B.
Abstract: Given the centrality of news media to democracy, it is concerning that public trust in media has declined in many countries. A potential mechanism that may reverse this trend is independent fact-checking to adjudicate competing claims in news stories. We undertake a survey experiment on a sample of 1608 Australians to test the effects of fact-checking on media trust using a real-life case study known as the "sports rorts" affair. We construct duplicate news articles from two national media outlets (i.e. ABC.net.au, news.com.au) containing a senior government minister's real-life false claim that public funds were not used for political advantage immediately before an election. Half of the participants are exposed to a third-party fact check, which confirms the Minister's claim is verifiably false, the other half are not. All respondents are asked to evaluate the story's and news outlets' trustworthiness. Contrary to our expectations we find a backfire effect whereby independent fact-checking decreases readers' trust in the original news story and outlet. This negative relationship is not conditional on partisanship or the media source. Our study provides a cautionary tale for those expecting third-party fact-checks to increase media trust and we outline several avenues by which fact-checkers might overcome this.